Chinese model of development in business culture - Aldabek, N.A.; Nursultanova, L. (Journal of Oriental Studies, 2022)
The purpose of this article is to study and evaluate the Chinese model in the development of culture in business relations, which has become an extremely relevant trend in recent years in China. In an environment where the number of urgent business problems is increasing, which cannot be solved without the concept of Chinese business culture, the development of a business model and new approaches becomes inevitable. Chinese business culture is based on the cooperation strategies and interactions that have characterized the international activities of Chinese companies in recent decades, as caution must be exercised due to differences in the political and cultural environment, which create risk and create uncertainty for foreign investors. Analyzing the values of Chinese companies, as well as considering the basic classification of corporate culture in Chinese business, can only be done by those who have deep and broad knowledge and the tools of critical thinking and action that allow them to maintain a clear mind and balanced decisions. Since the Chinese specific model is responsible for the development of business culture most relevant to China, use real practical examples in the field of science and technology in the ideas of promoting the Chinese model in business culture.